Current Legal Status of Payment Via E-Wallet in Vietnam - Hang, Nguyen Minh; Huong, Nguyen Thi (Journal of Posthumanism, 2025)
This research investigates and evaluates the current legal situation of payment via e-wallet in Vietnam. To be more specific, the paper analyses legal issues and current application, as well as proposes some solutions to complete the legal system in this field. The research uses qualitative methods combining theoretical analysis, survey and expert method. The findings reveal that in Vietnam, laws on payment via e-wallet include the State’s regulations, rules and guidelines to adjust, monitor and protect electronic payment via e-wallets, ensuring legitimacy, privacy and security for users, and promoting the development of cashless payment. These legal frameworks not only aim to adjust e-wallet service providers’ behaviours, but also protect consumers’ rights in transactions, contributing to the creation of a transparent, effective and reliable financial environment. However, there still exist several issues in laws on e-wallet payment, including (1) the lack of regulation on the maximum fine in administrative penalty for violations in e-commerce, (2) inconsistency of banned behaviours in e-commerce, (3) overlaps of remedial measures, (4) the lack of regulations on certain violations, (5) the inaccessibility to e-wallet of the disadvantaged in rural areas, i.e. farmers, those with low education levels or low income, and (6) trade in counterfeit and banned goods, goods of unknown origins and exploitation of e-commerce for fraud and appropriation of properties, which are getting more and more sophisticated regarding the scales and locations. From the authors’ perspectives, laws on e-wallet payment can be supplemented and amended in the following approaches. First, it should be clearly specified that properties within the payment-insured account are not subject to liquidation under the 2014 Law on Bankruptcy and the balance in the account must be returned timely and solely to the e-wallet users. Second, it should also be specified that the payment-insured account must be the e-wallet users’ current account when they transfer their money into an e-wallet; at the same time, the money transferred into the e-wallet must be stated for the payment-insured account. Finally, the deposit insurance mechanism should be applied for the balance in each e-wallet user’s account linked to the e-wallet.